Analisis Tingkat Kepuasan Pelanggan Kereta Api Angkutan Lebaran Di Pulau Jawa - Adi, Wahyu Tamtomo; Aghastya, Adya; Fadilah, Lina Nur (Politeknik Perkeretaapian Indonesia Madiun, 2017)
This research aimed to analyze customer satisfaction level of Lebaran trains in Java Island. Data collection was done through observation and spreading of questionnaires. The sample of this data collection is 206 respondents who traveled during Lebaran with train in Java Island. The result of the research by using Importance Performance Analysis method shows that the respondent's expectation for the train service is 82.8 percent while the respondent's satisfaction level is 65.4 percent. Customer Satisfaction Index for all attributes studied was 71.4 percent. Some of the attributes that need prioritized for improvement are considered inconsistent with the expectations of passengers: cleanliness and comfort toilets in the station and on the train, availability of facilities for the disabled, affordability of ticket prices and suitability of ticket prices with services. Other attributes that are important and considered satisfactory by respondens are information boards, station staff friendliness, cleanliness and convenience at the station, ticket service counter, train staff friendliness, cleanliness and convenience in trains, on-time departure train, punctuality of train arrival, travel time and ease of getting tickets.